The Role of Social Media in Shaping Students Narcissic Behavior - Andriani, Astri Dwi; Pupu Jamilah; Assyfa Azzahra (MultiTech Publisher, 2023)
The large number of students accessing the internet every year causes changes in behavior that occur during adolescence, one of which is narcissistic behavior that focuses on oneself when publishing oneself by displaying video content that is considered quite interesting. As technology develops, many digital applications emerge. The background to this research is the researcher's interest in the social phenomenon that is currently occurring, namely the use of social media TikTok among class XI students at Cimenteng Pagelaran High School. Likewise, the phenomenon of narcissistic behavior among teenagers has become commonplace. There are quite a lot of TikTok social media users at Cimenteng Pagelaran High School, TikTok social media is used as a medium to express self-confidence through video content. Therefore, researchers want to know whether the social media TikTok has a role in building self-confidence, thereby giving rise to students' narcissistic behavior. The research aims to determine the role of TikTok social media on students' narcissistic behavior. The subjects of this research consisted of 3 students who were active users of the social media TikTok in class XI Science at Cimenteng Pagelaran High School. The theoretical basis used was New Media from Pierre Levy. This research uses a qualitative method with a phenomenological approach. The data collection activities used were interviews and documentation. The research results show that social media has a role in shaping students' narcissistic behavior, because students who use TikTok social media become more confident because they are used to creating content that shows the special side of the informant, one of which is showing physicality and beauty.